2010
DOI: 10.3758/s13414-010-0047-9
|View full text |Cite
|
Sign up to set email alerts
|

Object based implicit contextual learning: a study of eye movements

Abstract: Implicit contextual cueing refers to a top-down mechanism in which visual search is facilitated by learned contextual features. In the current study we aimed to investigate the mechanism underlying implicit contextual learning using object information as a contextual cue. Therefore, we measured eye movements during an object-based contextual cueing task. We demonstrated that visual search is facilitated by repeated object information and that this reduction in response times is associated with shorter fixation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…Our prime measures of interest were the proportion of saccades directed towards the target cue, and fixation duration. From a basic learning perspective, one would predict that, as participants become increasingly familiar with the cue, encoding time should become shorter, resulting in shorter fixations times (e.g., Berlyne, 1958;Just & Carpenter, 1980;Rayner, 1978;van Asselen, Sampaio, Pina, & Castelo-Branco, 2011). In addition, as the target representation becomes known, there would be a decreasing necessity to look at the cue at all, which should be expressed in fewer saccades towards it.…”
mentioning
confidence: 99%
“…Our prime measures of interest were the proportion of saccades directed towards the target cue, and fixation duration. From a basic learning perspective, one would predict that, as participants become increasingly familiar with the cue, encoding time should become shorter, resulting in shorter fixations times (e.g., Berlyne, 1958;Just & Carpenter, 1980;Rayner, 1978;van Asselen, Sampaio, Pina, & Castelo-Branco, 2011). In addition, as the target representation becomes known, there would be a decreasing necessity to look at the cue at all, which should be expressed in fewer saccades towards it.…”
mentioning
confidence: 99%
“…Moreover, it also allows the use a variety of locations and stimuli. A number of studies have shown robust contextual cueing effects with respect to location regularity (Chun & Jiang, 1998;Chun & Jiang, 2003;Jiang & Chun, 2001) and object identity regularity (Chun & Jiang, 1999;van Asselen, Sampaio, Pina, & Castelo-Branco, 2011). Therefore, in our experimental paradigm, we manipulated individual object location and identity, as task-relevant and task-irrelevant regularities.…”
mentioning
confidence: 99%
“…Studies that have measured eye movements during the contextual cueing task have increased our understanding of the way in which learning facilitates visual search [van Asselen, Sampaio, Pina, & Castelo‐Branco, ; Brockmole & Henderson, ; Hout & Goldinger, ; Neider & Zelinsky, ; Peterson & Kramer, ; Tseng & Li, ]. Peterson and Kramer [] showed that in repeated displays, fewer fixations were required before the target was located, and the proportion of initial fixations that landed on the target was greater for repeated displays.…”
Section: Introductionmentioning
confidence: 99%
“…Hout and Goldinger [] termed this effect the spatial mapping hypothesis. Moreover, it has been shown that learning of the distractor items results in faster processing and recognition of these items, which itself leads to lower fixation duration [van Asselen et al., ]. Hout and Goldinger [] termed this the rapid identification and dismissal hypothesis.…”
Section: Introductionmentioning
confidence: 99%